Pengaruh NCT Dream sebagai Brand Ambassador, Promosi Penjualan dan Citra Merek terhadap Minat Beli Produk Mie Lemonilo di Balikpapan - Fitri Adijaya; Dewi Sartika (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of brand ambassadors, sales promotions, and brand image on the purchase intention of Mie Lemonilo products in Balikpapan. The research utilizes both primary and secondary data. Primary data were collected through a questionnaire distributed to followers of the Mie Lemonilo Instagram account in Balikpapan, while secondary data were gathered from various supporting sources. The population in this study consisted of all followers of the Mie Lemonilo Instagram account in Balikpapan, with a sample size of 100 individuals. The results of the study indicate that Brand Ambassador (X1) does not significantly influence the purchase intention of Mie Lemonilo. This suggests that the impact of the brand ambassador on consumer purchasing decisions in Balikpapan is not strong enough, possibly due to insufficient engagement or connection between the brand ambassador and consumers. In contrast, Sales Promotion (X2) has a significant positive impact on the purchase intention of Mie Lemonilo. This indicates that sales promotions, such as discounts or special offers, have a substantial effect in attracting consumer interest and increasing purchase intention in Balikpapan. Meanwhile, Brand Image (X3) does not show a significant influence on the purchase intention of Mie Lemonilo. This may be due to other factors being more dominant in influencing consumers’ purchase decisions, such as product price, quality, or social factors and market trends. This study provides insights that, although brand image is important, sales promotions play a more significant role in driving purchase intention for Mie Lemonilo products in Balikpapan. Therefore, the company should focus more on promotional strategies to increase sales while continuing to consider the role of brand ambassadors and brand image in their marketing strategies.